2016
DOI: 10.5152/tud.2016.90490
|View full text |Cite
|
Sign up to set email alerts
|

Catheter dwell time and diameter affect the recurrence rates after internal urethrotomy

Abstract: Objective: Cold-knife direct vision internal urethrotomy (DVIU) is frequently used as the first-line treatment for urethral stricture disease. Although the steps of the procedure are defined in detail, the duration of catheterization and the diameter of the catheter to be used after the operation are not clearly defined. The aim of this study is to evaluate the effects of catheter dwell time and diameter on recurrence rates of urethral stricture disease after DVIU. Material and methods:Data of 193 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The urethral incision was considered adequate when the cystoscope or urethrotome easily passed into the bladder. An indwelling catheter was generally left for 3-7 days in our series, although recent data and the AUA guidelines suggest that a urethral catheter may be safely removed 72 h after an uncomplicated DVIU [Wessells et al 2016;Yuruk et al 2016]. Post-DVIU treatment success was defined as lack of symptomatology and no further need for additional interventions, including self-dilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The urethral incision was considered adequate when the cystoscope or urethrotome easily passed into the bladder. An indwelling catheter was generally left for 3-7 days in our series, although recent data and the AUA guidelines suggest that a urethral catheter may be safely removed 72 h after an uncomplicated DVIU [Wessells et al 2016;Yuruk et al 2016]. Post-DVIU treatment success was defined as lack of symptomatology and no further need for additional interventions, including self-dilation.…”
Section: Methodsmentioning
confidence: 99%
“…An indwelling catheter was generally left for 3–7 days in our series, although recent data and the AUA guidelines suggest that a urethral catheter may be safely removed 72 h after an uncomplicated DVIU [Wessells et al . 2016; Yuruk et al . 2016].…”
Section: Methodsmentioning
confidence: 99%
“…Catheter characteristics could also play a role in stricture disease. EAU recommends avoiding non-coated latex catheterization due to the risk of urethritis/stricture [EAU: Strong] and the use of large catheters (> 18 Fr) for drainage-only purposes [EAU: Weak] [ [14][15][16][17].…”
Section: Stricture Preventionmentioning
confidence: 99%
“…11,18,19,21,34,35 Some reports found that leaving the urethral catheter in-situ for longer than 3-5 days was associated with increased recurrence. 36,37 Studies on the effects of the size of the urethral catheter on stricture recurrence rate is limited. Yuruk, E et al reported decreasing the catheter diameter from 22Fr to 18Fr significantly decreases stricture recurrence rates.…”
Section: Post-dviu Catheterizationmentioning
confidence: 99%
“…Yuruk, E et al reported decreasing the catheter diameter from 22Fr to 18Fr significantly decreases stricture recurrence rates. 37 It is postulated that larger bore urethral catheters potentially exert greater pressure on the urethral wall, reducing blood flow and hindering the re-epithelialization process. This subsequently leads to the healing of the incised urethra with fibrosis, causing stricture recurrence.…”
Section: Post-dviu Catheterizationmentioning
confidence: 99%